Effects of lotus (Nelumbo nucifera Gaertn.) stamen extract on growth performance, feed utilization and intestinal morphology of catfish (Clarias gariepinus) - Munglue, Phukphon (Asia-Pacific Journal of Science and Technology, 2016)
The effects of dietary supplementation of lotus (Nelumbo nucifera Gaertn.) stamen extract (NNSE) on growth performance, feed utilization efficiency and intestinal morphology of Catfish (Clarias gariepinus) were evaluated experimentally in a 7-week feeding trial. Fish with an initial weight of 12.54±0.64 g were completely randomized into 4 groups with 3 replications and reared in circular concrete tanks. Group 1, fish were fed the basal diets and served as the control group. Groups 2-4, fish were fed the diets supplemented with 0.1, 0.5 and 1% of NNSE, respectively. At the end of experiment, it was found that fish fed the diets containing NNSE at different levels significantly increased weight gain, specific growth rate and feed conversion ratio compared to the control (P<0.05). No significant differences were observed in the survival rate and the relative weights of internal organs between the groups (P>0.05). Villi heights and widths, muscularis thickness and goblet cell number in anterior and posterior portion of fish intestines observed under the light microscope were significantly increased in the experimental groups compared to the control group (P<0.05). Additionally, feeding behavior, palatability and feed acceptability did not differ among the groups. The optimal level of NNSE observed was 0.1%. Taken together, these findings reveal that NNSE could be applied in fish feed as a natural feed additive without negative side-effects to improve growth, feed utilization and intestinal morphology in Catfish.